Synergistic Effect of L-Carnosine and Hyaluronic Acid in Their Covalent Conjugates on the Antioxidant Abilities and the Mutual Defense against Enzymatic Degradation - Valeria Lanza; Valentina Greco; Eleonora Bocchieri; Sebastiano Sciuto; Rosanna Inturri; Luciano Messina; Susanna Vaccaro; Francesco Bellia; Enrico Rizzarelli (Antioxidants, 2022)
Hyaluronic acid (Hy) is a natural linear polymer that is widely distributed in different organisms, especially in the articular cartilage and the synovial fluid. During tissue injury due to oxidative stress, Hy plays an important protective role. All the beneficial properties of Hy make the polymer attractive for many biomedical uses; however, the low stability and short biological half-life limit Hy application. To overcome these problems, the addition of small antioxidant molecules to Hy solution has been employed to protect the molecular integrity of Hy or delay its degradation. Carnosine (β-alanyl-L-histidine, Car) protects cells from the damage due to the reactive species derived from oxygen (ROS), nitrogen (RNS) or carbonyl groups (RCS). Car inhibits the degradation of hyaluronan induced by free radical processes in vitro but, like Hy, the potential protective action of Car is drastically hampered by the enzymatic hydrolysis in vivo. Recently, we conjugated Hy to Car and the derivatives (HyCar) showed protective effects in experimental models of osteoarthritis and rheumatoid arthritis in vivo. Here we report the antioxidant activity exerted by HyCar against ROS, RNS and RCS. Moreover, we tested if the covalent conjugation between Hy and Car inhibits the enzymatic hydrolysis of the polymer and the dipeptide backbone. We found that the antioxidant properties and the resistance to the enzymatic hydrolysis of Hy and Car are greatly improved by the conjugation.